Numerical investigation of fluid dynamics phenomena in external gear pump - Bilalov, Ruslan Al’fredovich; Smetannikov, Oleg Yur’yevich (Computational Continuum Mechanics, 2020)
A three-dimensional numerical model able to describe the performance of a gear pump taking into account turbulence and cavitation is presented. The computational model is implemented in the ANSYS CFX software package. As a method for modeling moving boundaries (taking into account the rotation of gears), the method of "immersed solid" is chosen. A homogeneous two-phase model is used to describe the flow of a viscous incompressible fluid with the formation of cavitation. The adequacy of the developed model is checked; the analysis of the numerical stability and convergence of the solution is carried out. With this model, a number of computational experiments were carried out at the experimental design stage to create a fuel system for a promising gas turbine engine. The technical characteristics of the pump, such as the flow rate, presence and degree of cavitation, were checked. Simulation results for different pump operating modes are analyzed. Comparison of the numerical results for single-phase and two-phase flow is performed. The places of cavitation formation and its level are shown and justified. The localization and volume of cavitation areas, cavitation concentration, and the level of its possible influence on the consumable-technical and strength characteristics of the product are examined in relation to the rotational speed of gears. It has been found that cavitation areas are formed, especially, at high gear speeds. The simulation results are presented in the form of graphical functional dependencies and contour plots. The developed numerical model of the gear pump makes it possible to carry out computational experiments instead of expensive full-scale ones, and to give recommendations for preventive improvement of the design, even before the manufacture of prototypes of the product.